Effects of Physical Exercise on the P300 of Elderly With Alzheimer's Disease - Pedroso, Renata Valle [UNESP]; Cancela, Jose Maria; Ayan, Carlos; Stein, Angelica Miki [UNESP]; Fuzaro, Gilson [UNESP]; Costa, Jose Luiz Riani [UNESP]; Fraga, Francisco J.; Santos-Galduroz, Ruth Ferreira [UNESP] (Human Kinetics Publ Inc, 2018)
Background: Evidence regarding the benefits of physical activity on the mental processing information of patients with Alzheimer's disease assessed objectively is scarce and can be observed through event-related potentials, such as the P300. The aim of the study was to identify the effects of physical exercises on mental processing information in the elderly with Alzheimer's disease through neurophysiological measures (P300 amplitude and latency) and reaction time. Methods: A total of 31 patients with Alzheimer's disease participated in this study: 14 in functional exercise (FE) group and 17 in social gathering (SG) group who carried out three 1-hour sessions per week of FE and SG activities, respectively, for a 12-week period. All groups performed an auditory oddball task. A healthy elderly control group also participated. Results: Significant (P < .05) improvements were observed as a reduction of reaction time after intervention in the FE group (pre = 421.5 ms and post = 360.9 ms). Also, an increase of P300 amplitude at central midline (pre = 5.9 mu V and post = 6.9 mu V) and parietal midline (pre = 4.7 mu V and post = 5.7 mu V) was observed in the FE. Finally, a decrease in the P300 latency at frontal midline (pre = 377 ms and post = 367 ms) was observed in the SG after the intervention. Conclusion: Physical exercise decreases reaction time and suggests a recovery in cortical activity, whereas SG activities could probably facilitate information processing.
Keywords: gerontology; mental health; neuroscience; rehabilitation